PENGARUH MOTIVASI KERJA, KEMAMPUAN KERJA, DAN IKLIM ORGANISASI TERHADAP PRESTASI KERJA KARYAWAN PADA YAYASAN PENDIDIKAN MEDIKA CENDIKIA KOTA METRO LAMPUNG - Marsono B. Marsono B. (Derivatif : Jurnal Manajemen, 2018)
Human Resources is a Company asset that must constantly be improved. If the SDM on a good company, it will have a positive impact in creating a positive image (good image). A good company image in the eyes of the people will bring good luck to the business development of the company. As the human resources that are reliable, the employee is required to be able to work properly, discipline and certainly most proud of is able to achieve maximum performance. In addition to technology, supporting equipment use, environment, loyalty, and the ability of employees, motivation, ability to work and organizational climate also has a very important role.  The background of this research on the problem of discipline employees of YAYASAN PENDIDIKAN MEDIKA CENDIKIA Metro City that will have an impact on employee job performance both in quality and quantity.  This study focuses on the effect of work motivation, ability to work and organizational climate on employee performance at YAYASAN PENDIDIKAN MEDIKA CENDIKIA Metro City.In this study using the data collection methods with a survey that is research taking samples for examination and use questionnaires as the principal means of collecting data. Data analysis methods used are quantitative.The test results show that the hypothesis has been proved to be no direct influence on the working motivation variable work achievement, the variable Work Ability to Work Performance and Organizational Climate variables on Job Performance. Furthermore, with the same variable Work Motivation, Ability Work and Organizational Climate determine which variables work achievement of 73.20 percent (R Square = 0.732). Based on the value to indicate that work motivation is more significant than the variable ability thitung work and organizational climate variables (motivation thitung work = 9.193 is greater than the value thitung the ability to work = 3.092 and thitung the organizational climate = 1.705) Keywords: work motivation, work ability, organizational climate, job performance